Factors Influencing Community Fishers' Leadership Engagement in International Small-Scale Fisheries - Sutton, Abigail M.; Rudd, Murray A. (Frontiers in Marine Science, 2016)
Local leadership is crucial to the functioning of local organizations in small-scale fishing (SSF) communities. By analyzing local leadership experiences of 54 international SSF researchers and practitioners, we aim in this paper to fill knowledge gaps that recent research has identified regarding our understanding of factors that influence the effectiveness of local leadership. Influencing factors are organized using modified versions of the Institutional Analysis and Development (IAD) framework, the Value-Belief-Norm (VBN) theory, and Schwartz’s theory of cultural values. We identified factors that help shape leadership engagement and effectiveness at multiple levels, including: precursors to individual action that relate to potential SSF leaders’ perceptions of threat and opportunities; institutional constraints at the individual level and community level; and high level governance issues. Precursors to individual action were numerous and multi-faceted, and individual behaviors were shaped by core values and attitudes, culture, experiences, and education. Motivation to participate in leadership can either be altruistic in nature or oriented towards self-enhancement. A lack of motivation for leadership could be attributed to the individualistic nature of many fishers. The availability of capital assets can facilitate or hinder participation in leadership. Individuals who may be willing to take on leadership roles were often hindered by lack of money and time, low educational attainment, or poor social cohesion among community members. The interactions between leaders and followers were crucial for effective leadership, especially a leader’s perceived legitimacy and the ability of a community to groom appropriate successors. At the higher level, constant policy change and the resulting uncertainty were linked to decreasing motivation and apathy regarding SSF management at the local level, and disintegrating relationships between government level and local level actors. Our research highlights how local leadership and context are linked, and suggests potential researchable hypotheses that would in the future help further advance empirical and theoretical understanding of leadership influences in SSFs.